2020
DOI: 10.21601/ortadogutipdergisi.626306
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the success of supraclavicular blockade performed under general anesthesia in arthroscopic surgery of the shoulder by using Perfusion Index

Abstract: To cite this article: Ceylan A, Eşkin MB. Evaluation of the success of supraclavicular blockade performed under general anesthesia in arthroscopic surgery of the shoulder by using Perfusion Index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…18 The use of ultrasonic-guided supraclavicular blockade has become more common in arthroscopic shoulder surgeries as an alternative to anesthesia and analgesia. Ceylan and Eskin 19 conducted a study to determine the effectiveness of the perfusion index (PI), which measures the increase in peripheral perfusion of the upper extremity, in assessing the success of a single dose of supraclavicular nerve block under general anesthesia. The study found that the PI, measured noninvasively with a pulse oximetry probe, can be used to evaluate the success of the nerve block with reliability.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…18 The use of ultrasonic-guided supraclavicular blockade has become more common in arthroscopic shoulder surgeries as an alternative to anesthesia and analgesia. Ceylan and Eskin 19 conducted a study to determine the effectiveness of the perfusion index (PI), which measures the increase in peripheral perfusion of the upper extremity, in assessing the success of a single dose of supraclavicular nerve block under general anesthesia. The study found that the PI, measured noninvasively with a pulse oximetry probe, can be used to evaluate the success of the nerve block with reliability.…”
Section: Clinical Applicationsmentioning
confidence: 99%